EFFECT OF VIRTUAL REALITY EXERCISES TO LEARN TRIPLE JUMP PERFORMANCE FOR STUDENTS - Waad Gharbi Saleh; Mohammed Issam Dara; Hamad Abdul Salam Sultan (Journal Olahraga Rekat (Rekreasi Masyarakat), 2025)
Background. The integration of advanced technology in sports education has created new possibilities for improving the teaching and learning process of complex motor skills. The triple jump, as one of the technically demanding track and field events, requires precise coordination, rhythm, and execution, making it challenging for students to master through traditional instruction alone. Objectives. This study aimed to design an educational program based on virtual reality (VR) technology and to investigate its effectiveness in enhancing the technical performance of the triple jump among university students. Method. The research population consisted of second-year students at the College of Physical Education and Sports Sciences, University of Kirkuk, during the academic year 2024/2025, totaling 80 students. From this population, a random sample of 36 students was selected and divided into two equal groups: an experimental group (n = 18) taught using the VR-based program and a control group (n = 18) taught using conventional methods. Several students were excluded due to prior experience, failure in the course, incomplete participation, or repeated absences to ensure sample homogeneity. Data were collected through pre- and post-tests assessing technical performance using video analysis. Results. The results show that the experimental group achieved a higher average score (M = 8.36, SD = 0.54) than the control group (M = 5.59, SD = 0.84). The calculated t-value was -11.783 with a significance level of 0.000 (p < 0.05), indicating a statistically significant difference in favor of the experimental group. These findings confirm that the use of virtual reality-based education programs is more effective than traditional methods in improving technical performance in long jump among students. Conclusion. The study concludes that VR-based exercises represent an effective approach to teaching the technical components of the triple jump. Accordingly, it is recommended that such technology be adopted in sports education curricula to enhance students’ practical skills and learning outcomes.